From tau phosphorylation to tau aggregation: what about neuronal death?. (26th July 2010) - Buée, Luc; Troquier, Laëtitia; Burnouf, Sylvie; Belarbi, Karim; Van der Jeugd, Anneke; Ahmed, Tariq; Fernandez-Gomez, Francisco; Caillierez, Raphaelle; Grosjean, Marie-Eve; Begard, Séverine; Barbot, Bérangère; Demeyer, Dominique; et al.
Abstract : Tau pathology is characterized by intracellular aggregates of abnormally and hyperphosphorylated tau proteins. It is encountered in many neurodegenerative disorders, but also in aging. These neurodegenerative disorders are referred to as tauopathies. Comparative biochemistry of the tau aggregates shows that they differ in both tau isoform phosphorylation and content, which enables a molecular classification of tauopathies. In conditions of dementia, NFD (neurofibrillary degeneration) severity is correlated to cognitive impairment and is often considered as neuronal death. Using tau animal models, analysis of the kinetics of tau phosphorylation, aggregation and neuronal death in parallel to electrophysiological and behavioural parameters indicates a disconnection between cognition deficits and neuronal cell death. Tau phosphorylation and aggregation are early events followed by cognitive impairment. Neuronal death is not observed before the oldest ages. A sequence of events may be the formation of toxic phosphorylated tau species, their aggregation, the formation of neurofibrillary tangles (from pre-tangles to ghost tangles) and finally neuronal cell death. This sequence will last from 15 to 25 years and one can ask whether the aggregation of toxic phosphorylated tau species is a protection against cell death. Apoptosis takes 24 h, but NFD lasts for 24 years to finally kill the neuron or rather to protect it for more than 20 years. Altogether, these data suggest that NFD is a transient state before neuronal death and that therapeutic interventions are possible at that stage.